Prevalence of nasal carriage of MRSA in diabetic patients attending the outpatient department - Bhoi, Priyadarshini; Otta, Sarita; Swain, Bichitrananda; Kar, Bikash Ranjan (International Journal of Research in Medical Sciences, 2020)
Background: Up to 30% of the human population is asymptomatically colonized with nasal Staphylococcus aureus. Study was done to determine the prevalence and risk factors for MRSA colonization as nasal carrier in a population of outpatients with diabetes. Methods: The study enrolled patients with diabetes from whom nasal swabs were obtained and were analyzed for presence of MRSA. Results: Out of the 402 patients evaluated, 254 (63.18%) were colonized with S. aureus and 164 (64.56%) of them were MRSA. Conclusions: Diabetes have more propensity for MRSA colonization than non-diabetic patients. A better understanding of the epidemiology and risk factors for nasal MRSA colonization in the persons with diabetes may have significant implications for the treatment and prevention of MRSA infections.